Pengaruh Literasi Keuangan terhadap Keberlanjutan Bisnis UMKM di Indonesia - Mohammad Chaidir; Grace Yulianti; Ruslaini Ruslaini (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
This study examines the impact of financial literacy on the business sustainability of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. MSMEs play a strategic role in the national economy but face challenges such as limited access to financing and suboptimal financial management. Financial literacy is key in helping MSMEs manage cash flow, access formal financial services, and make sound investment decisions. This research employs a literature review method to evaluate the relationship between financial literacy and MSME business sustainability. The findings reveal that financial literacy influences financial decision-making, enhances access to financing, and reduces financial risks. Additionally, aspects such as budget planning, debt management, and the use of financial technology significantly affect MSME sustainability. This study provides strategic recommendations, including implementing integrated financial literacy education programs utilizing digital technology and collaborating with financial institutions to support sustainable MSME growth.